Plants invade the land : evolutionary and environmental perspectives - Gensel, Patricia G., 1944-; Edwards, D. (Dianne) (Critical moments in paleobiology and earth history series., 2001)
What do we now know about the origins of plants on land, from an evolutionary and an environmental perspective? The essays in this collection present a synthesis of our present state of knowledge, integrating current information in paleobotany with physical, chemical, and geological data.